DISTRIBUTION FACTORS, RICE PRICE FLUCTUATION, AND MUSLIM FARMERS' WELFARE IN MARE - Syakila; Arifin Sahaka; Andi Ika Fahrika (Islamic Economic and Business Journal, 2026)
Abstrak Penelitian ini menganalisis pengaruh faktor distribusi terhadap kesejahteraan petani padi muslim melalui fluktuasi harga beras di Kecamatan Mare, Kabupaten Tulang. Pendekatan asosiatif-kausal kuantitatif diterapkan pada 100 petani padi Muslim yang dipilih melalui purposive sampling. Data primer dikumpulkan menggunakan kuesioner skala Likert lima poin yang didistribusikan secara online, dan dianalisis menggunakan Structural Equation Modeling based on Partial Least Squares (SEM-PLS) dengan SmartPLS 4. Model pengukuran memenuhi kriteria validitas konvergen, validitas diskriminan, dan keandalan, sedangkan model struktural menunjukkan kesesuaian yang dapat diterima (SRMR = 0,082). Hasil penelitian menunjukkan bahwa faktor distribusi memiliki efek langsung positif yang signifikan terhadap fluktuasi harga beras (β = 0,746; p = 0,000) dan kesejahteraan petani (β = 0,499; p = 0,000). Fluktuasi harga beras juga secara signifikan memediasi pengaruh faktor distribusi terhadap kesejahteraan petani (efek tidak langsung = 0,377; p = 0,0002). Temuan ini menunjukkan bahwa sistem distribusi yang efisien, transparan, dan merata, konsisten dengan prinsip keadilan dan maslahah Syariah, sangat penting untuk menstabilkan harga beras dan meningkatkan kesejahteraan petani.   Abstract This study analyzed the effect of distribution factors on the welfare of Muslim rice farmers through rice price fluctuation in Mare Subdistrict, Bone Regency. A quantitative associative-causal approach was applied to 100 Muslim rice farmers selected through purposive sampling. Primary data were collected using a five-point Likert-scale questionnaire distributed online, and were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4. The measurement model satisfied the criteria for convergent validity, discriminant validity, and reliability, while the structural model showed an acceptable fit (SRMR = 0.082). The results showed that distribution factors had a significant positive direct effect on rice price fluctuation (β = 0.746; p = 0.000) and on farmers' welfare (β = 0.499; p = 0.000). Rice price fluctuation also significantly mediated the effect of distribution factors on farmers' welfare (indirect effect = 0.377; p = 0.0002). These findings indicate that efficient, transparent, and equitable distribution systems, consistent with the Sharia principles of justice and maslahah, are essential for stabilizing rice prices and improving farmers' welfare. Abstract This study analyzed the effect of distribution factors on the welfare of Muslim rice farmers through rice price fluctuation in Mare Subdistrict, Bone Regency. A quantitative associative-causal approach was applied to 100 Muslim rice farmers selected through purposive sampling. Primary data were collected using a five-point Likert-scale questionnaire distributed online, and were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS 4. The measurement model satisfied the criteria for convergent validity, discriminant validity, and reliability, while the structural model showed an acceptable fit (SRMR = 0.082). The results showed that distribution factors had a significant positive direct effect on rice price fluctuation (β = 0.746; p = 0.000) and on farmers' welfare (β = 0.499; p = 0.000). Rice price fluctuation also significantly mediated the effect of distribution factors on farmers' welfare (indirect effect = 0.377; p = 0.0002). These findings indicate that efficient, transparent, and equitable distribution systems, consistent with the Sharia principles of justice and maslahah, are essential for stabilizing rice prices and improving farmers' welfare.